MILITARY IMAGE OF A UKRAINIAN MAN IN THE 1945–1989 GRAPHIC DESIGN OF THE DIASPORA - Косів, В. М. (Art and Design, 2019)
The purpose of the study is to identify the peculiarities of a Ukrainian Man visual representation in the 1945–1989 graphic design of the Ukrainian diaspora. The methodology of this research is based on iconographic and semiotic analysis, as well as the application of gender studies approach. Graphic design is discussed as visual communication, methods of the «new art history» were applied. In the circles of post-war Ukrainian emigration, the spirit of general mobilization and readiness for the struggle for the liberation of Ukraine was spreading; therefore, the image of a Ukrainian Man in visual communication was mainly associated with armed struggle. Images of an Ancient Rus’ Warrior, a Cossack, a Sich Rifleman accompanied a narrative about the continuity of this struggle for centuries. At the same time, allegorical pseudo-religious images spread, where Ukrainian liberation was treated as a «holy» struggle. The most common and semantically flexible was the Cossack image. It could remind a concrete historical period, denote all the fighters for the freedom of Ukraine or embody all the Ukrainians. Over time, when the idea of armed struggle lost its relevance, militaristic images, as well as men’s images in general, becam less common. The scientific novelty is defined by a little-known material as well as the connections between ideological constructions and visual communication. Practical significance. The research reveals the contexts and explains the iconography of militaristic images of Ukrainians in graphic design of the diaspora from 1945–1989. This will allow for appropriate generalizations regarding a visual representation of Ukrainian identity.